Riesgos ergonómicos en la fase de pos- cosecha y su incidencia en las alteraciones musculo - esqueléticas de los trabajadores de la florícola Safety Flowers S.A, y plan de capacitación. - Guerra Palma, Jeomayra Maricela (2017)
The research is based on the application of an ergonomic study in the area of Post-harvest of Floriculture SAFETY FLOWERS, and muscule-skeletal affections, which they were performed by applying the method REBA and a survey of the Nordic questionnaire. It began identifying the presence of workers´ disorders because the company keeps track a record of high absenteeism (shoulders pain, neck, back etc.) to scientifically demonstrate this data reported by the company, we make a matrix risk identification, where it is shown that in Post-harvest there are ergonomic hazards with high score, so this research focuses on jobs in the mentioned area such as skater, sorting, classification and packaging with an ergonomic assessment by analytical tools that determine the degree of ergonomic hazard is which allowed to determine risk factors to obtaining a high risk rating in the following jobs, skater with a risk level 10, sorter with a risk of 9, packager with a risk of 14; within more muscle-skeletal disorders there is a higher incidence in such neck, elbow, forearm so it was detected awkward postures, repetitive motions, and improper lifting loads, based on these results it was determined procedures for workers to be trained by the security officer and the constant boss post harvest´s supervision in the right lifting loads, apply breaks and the proper handling of awkward postures allowing workers more efficient in their daily activities.